2009
DOI: 10.1038/nrurol.2009.102
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive nephrectomy for metastatic RCC in the era of targeted therapy

Abstract: Metastatic renal cell carcinoma (RCC) has traditionally been associated with a poor prognosis with few effective treatments. In the multimodal treatment of metastatic RCC, cytoreductive nephrectomy (CN) became the standard of care after two randomized trials demonstrated a benefit in overall survival in patients who received CN prior to treatment with interferon. More recently, several agents (sunitinib, sorafenib, temsirolimus, everolimus and bevacizumab) have been developed that target angiogenesis and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 78 publications
1
21
0
2
Order By: Relevance
“…Immunotherapy, such as interferon-α and high-dose interleukin (IL)-2, results in only limited response rates of 15% to 20% [5,6]. Recent advances in targeted molecular therapies with angiogenesis inhibitors, tyrosine kinase inhibitors, and combination treatment modalities have demonstrated improved outcomes; however, the response rates for these novel therapies still remain low [7].…”
Section: Introductionmentioning
confidence: 99%
“…Immunotherapy, such as interferon-α and high-dose interleukin (IL)-2, results in only limited response rates of 15% to 20% [5,6]. Recent advances in targeted molecular therapies with angiogenesis inhibitors, tyrosine kinase inhibitors, and combination treatment modalities have demonstrated improved outcomes; however, the response rates for these novel therapies still remain low [7].…”
Section: Introductionmentioning
confidence: 99%
“…A combined analysis of these SWOG and EORTC trials confirmed a longer median survival in the nephrectomy/IFN-α group [8]. In theory, tumour bulk may act as a sink absorbing antibodies and anticancer cells [9] and/or tumour releasing pro-angiogenic factors (VEGF and PDGF) [10]. The role of nephrectomy in the management of mRCC is less well established in the era of targeted therapies.…”
Section: Introductionmentioning
confidence: 99%
“…16, 17 Although cytoreductive nephrectomy followed by systemic therapy is the current standard of care in the treatment of metastatic RCC, 35 critics of that approach argue that surgery could introduce unnecessary morbidity and mortality in this patient population and that it could potentially delay or even prevent these patients from receiving systemic therapy. 18 …”
Section: Discussionmentioning
confidence: 99%